Peran Guru Dalam Pembelajaran Pada Masa Pandemi Covid-19 Siswa Kelas VI SDN Bukit Permai Tahun Pelajaran 2020/2021 - Evy Velia Yahya; H.A. Hari Witono; Muhammad Tahir (Journal of Science Instruction and Technology, 2021)
This study aims to describe the role of teachers in learning during the covid-19 pandemic for grade VI students at SDN Bukit Permai. This research is motivated by the role of teachers in implementing learning during a pandemic or distance learning. The research location is SDN Bukit Permai, Sumbawa. The primary data sources are the teachers of class VI A and VI B and also the principal. This study uses descriptive qualitative research methods. Data collection techniques using interviews, observation, and documentation. Data analysis using Milles and Huberman models, namely data condensation, data presentation, and drawing conclusions. The results of the study are: 1) The teacher's role as a teacher learning designer makes learning plans, namely online lesson plans consisting of an introduction, core, and closing. The teacher also prepares media in the form of videos that are downloaded on YouTube as well as the selection of media and methods that are in accordance with current conditions. 2) The role of the teacher as a learning manager, the teacher uses various supporting applications such as WhatsApp, google meet, and also toom. Communication regarding lesson information is done through Whatsapp while material delivery is done through google meet and also a zoo. 3) Teachers as learning directors always give rewards to students who always show a positive attitude during and after learning takes place. 4) The teacher as an evaluator, in giving assignments is carried out after each lesson which will be collected once a week. 5) Teachers as counselors, teachers help students who have problems in participating in learning and outside learning to increase the potential of students.